ปัจจัยส่งเสริมการจัดการศึกษาที่ส่งผลต่อคุณภาพนักเรียน ในภาคตะวันออกเฉียงเหนือ The Supporting Factors of the Educational Management Affecting Students ’ Quality in the Northeastern Part of Thailand - สินธุวงษานนท์, มานะ (วารสารศึกษาศาสตร์ มหาวิทยาลัยบูรพา, 2014)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาระดับคุณภาพนักเรียน ด้านความเก่ง ด้านความดีและด้านการมีความสุข เพื่อศึกษาระดับความสำคัญขององค์ประกอบคุณภาพนักเรียนในภาคตะวันออกเฉียงเหนือ และความกลมกลืนกับข้อมูลเชิงประจักษ์ และเพื่อศึกษาความสัมพันธ์ของปัจจัยส่งเสริมการจัดการศึกษาระดับนักเรียนระดับห้องเรียน และระดับโรงเรียน ที่ส่งผลต่อคุณภาพนักเรียนในภาคตะวันออกเฉียงเหนือ โดยตัวแปรตามองค์ประกอบคุณภาพนักเรียนประกอบด้วย 1) ความเก่ง 2) ความดี และ 3)การมีความสุข ซึ่งความเก่ง วัดจากความสามารถใน3 ด้าน คือ 1) ความสามารถในการเรียนรู้ 2)ความสามารถในการวางแผนการทำงาน และ 3)ความสามารถในการตัดสินใจและแก้ปัญหาความดีวัดจากพฤติกรรมใน 3 ด้าน คือ 1) การควบคุมตนเอง 2) การเห็นใจผู้อื่น และ3)ความรับผิดชอบ การมีความสุขวัดจากสภาพความพึงพอใจใน 3 ด้าน คือ 1) ความภูมิใจในตนเอง 2) ความพอใจในชีวิต และ 3) ความสุขสงบทางใจ ส่วนตัวแปรอิสระปัจจัยส่งเสริมการจัดการศึกษาปัจจัยระดับนักเรียน ประกอบด้วย 1) ความสนใจใฝ่รู้ 2) บรรยากาศในครอบครัว 3) ความพร้อมที่จะเรียน และ 4) กระบวนการพัฒนาตนเองปัจจัยระดับห้องเรียน ประกอบด้วย 1) ความกระตือรือร้น 2) ความรอบรู้ 3) การให้คำปรึกษาและ 4) การจัดการชั้นเรียน ปัจจัยระดับโรงเรียนประกอบด้วย 1) โครงสร้างการบริหารโรงเรียน 2) พันธกิจที่ชัดเจน 3) ความกลมเกลียว 4) การมีส่วนร่วมของผู้ปกครอง และ 5) กระบวนการบริหารคุณภาพกลุ่มตัวอย่างที่ใช้ในการวิจัยประกอบ ด้วยผู้บริหารโรงเรียนในภาคตะวันออกเฉียงเหนือ จำนวน 40 คน ครูผู้สอนชั้นมัธยมศึกษาปีที่ 3 จำนวน 218 คน นักเรียนชั้นมัธยมศึกษาปีที่ 3 จำนวน 4,200 คน รวมกลุ่มตัวอย่างทั้งสิ้นจำนวน 4,458 คน เครื่องมือที่ใช้ในการวิจัย ในการวัดตัวแปรตามเป็นแบบประเมินคุณภาพนักเรียน ส่วนวัดตัวแปรอิสระเป็นแบบมาตราส่วนประมาณค่า 5 ระดับ สถิติที่ใช้ในการวิเคราะห์ระดับคุณภาพนักเรียนใช้ค่าเฉลี่ยและค่าเบี่ยงเบนมาตรฐาน การวิเคราะห์ระดับความสำคัญขององค์ประกอบคุณภาพนักเรียน และความกลมกลืนกับข้อมูลเชิงประจักษ์ใช้การวิเคราะห์องค์ประกอบเชิงยืนยันขั้นตอนที่ 2 ด้วยโปรแกรม LISREL 8.72 การวิเคราะห์พหุระดับด้วยโปรแกรม HLM 6.02 Student Version ผลการวิจัย 1. ระดับคุณภาพโดยรวมอยู่ในระดับปานกลาง เมื่อพิจารณาเป็นรายด้านพบว่าอยู่ในระดับปานกลางทุกด้าน โดยเรียงลำดับจากมากไปหาน้อยดังนี้ คือ ด้านการมีความสุข ด้านความเก่ง และด้านความดี ตามลำดับ 2. องค์ประกอบด้านคุณภาพนักเรียนมีความกลมกลืนกับข้อมูลเชิงประจักษ์และพบว่าระดับความสำคัญขององค์ประกอบคุณภาพนักเรียน มีค่าเป็นบวกเรียงลำดับความสำคัญในการอธิบายคุณภาพนักเรียนได้ดังนี้ คือด้านการมีความสุข ด้านความดี และด้านความเก่งตามลำดับ 3. การวิเคราะห์พหุระดับปัจจัยส่งเสริมการจัดการศึกษาที่ส่งผลต่อคุณภาพนักเรียนในภา8ตะวันออกเฉียงเหนือ ในระดับนักเรียน พบว่ากระบวนการพัฒนาตนเอง และความพร้อมที่จะเรียนส่งผลต่อคุณภาพนักเรียนในทางบวกในระดับห้องเรียน การจัดการชั้นเรียน และความกระตือรือร้นของครู ส่งผลต่อคุณภาพนักเรียนในทางบวก ส่วนความรอบรู้ของครูส่งผลต่อคุณภาพนักเรียนในทางลบ ในระดับโรงเรียนพบว่า โครงสร้างการบริหารโรงเรียนและกระบวนการบริหารคุณภาพส่งผลต่อคุณภาพนักเรียนในทางบวก The purposes of this dissertation were to study the levels of students’ quality on the aspects of intelligence , goodness , and happiness ; to study the factors of students’ quality and the accordance of those factors with the evident data ; and to study the affecting of the supporting factors of the educational management to the students’ quality in the student, the class , and the school level. The dependent variables were intelligence, goodness, and happiness. The intelligence of students was assessed by their abilities in learning, planning and decision making. The goodness was evaluated by their self - controlling, sympathy, and responsibility. The happiness was appraised by their self - esteem,life satisfaction, and peaceful mind. The independent variables were the supporting factors devided into three levels : the student, the class, and the school one. The student level consisted of four factors of the learners : 1) the inquiring interest, 2) the home atmosphere, 3) the readiness to study, and 4) the self- development processes. The class level was composed of four factors of the teacher : 1) the enthusiasm, 2) the mastery, 3) the counseling, and 4) the classroom management. The school level was devided into five factors of the administration : 1) the school structure, 2) the clear school mission , 3) the cohesiveness, 4) the parent participation, and 5) the quality management. The 4,394 samples of this study were 40 school administratiors, 218 teachers of Matayomsuksa 3 , and 4,136 Matayomsuksa 3 students. The research instrument for gathering data of the dependent variables was the Students’ Quality Evaluation Form , and the another for gathering data of the independent variables was the rating scale questionnaire. The data were analyzed to find the statistical values as mean, standard deviation, the confirmatory factor analysis by the LISREL 8.72 Program and the multi – level analysis by the HLM 6.02 Student Version Program. The research findings were as follows : 1.The students’ quality as a whole was in the moderate level. When considered in each aspect, everyone was also in the moderate level too ; ( the happiness ; the intelligence ; and the goodness respectively). They showed that the students’ quality was in the moderate level both as a whole and as each aspect. 2. The confirmatory factor analysis in step found that the students’ quality factors and the evident data were compatible. The importance of the students’ quality showed that every aspect was positive, which ranked by their mean as happiness, goodness, and intelligence, respectively. 3 . The results of multi - level analysis of data of the supporting factors of the educational management in the levels of students, classes, and schools that affecting the students’ quality in the Northeastern Part of Thailand were as the following : In the students level, the self – development and readiness to study affected the students’ quality positively. In the class level, the teachers’ enthusiasm and classroom management affected the students’ quality positively, but the teacher’s mastery affected the students’ quality negatively. In the school level, the school structure and the quality management affected the students’ quality positively.